Radiocarbon (14C) Analysis of Carbonaceous Aerosols: Revisiting the Existing Analytical Techniques for Isolation of Black Carbon - Dasari, Sanjeev; Widory, David (Frontiers in Environmental Science, 2022)
Air pollution, a complex cocktail of different components, exerts an influence on climate/human; health both locally and away from source regions. The issue of air pollution is often closely linked; to carbonaceous aerosols, the assessment of climate/air quality/health impact of which remains associated with large uncertainties. Black carbon (BC)—a product of incomplete combustion—is a potent climate warming agent and one of the central components to this issue. An accurate; knowledge of BC emitting sources is necessary for devising appropriate mitigation strategies and; policies to reduce the associated climate/environmental burden. The radiocarbon isotope (14C or carbon-14) fingerprinting allows for an unambiguous and quantitative constraining of the BC sources and is therefore a well-popularized method. Here, we review the existing analytical techniques for the isolation of BC from a filter matrix for conducting 14C-based investigations. This work summarizes the protocols in use, provides an overarching perspective on the state-of- the-art and recommendations for certain aspects of future method development.